2020
DOI: 10.17159/2520-9868/i80a03
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive skills and accounting graduates' employment prospects: Are South African employers calling for pervasive skills when recruiting?

Abstract: In response to the pressures of globalisation and information technology, accounting practitioners are generally expected to demonstrate greater capacity in pervasive or generic skills. Universities offering accounting programmes in South Africa have revised accounting degree curricula to provide an added focus on pervasive skills. However, it remains unclear whether such interventions strengthen the position of accounting graduates in the job-seeking process, nor is it clear which of the many possible pervasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Inadequate of technological practices in tertiary institutions is another challenge that has been highlighted in the literature (Johnson et al, 2016). According to Mhlongo (2020), trainee accountants are faced with the application of IT skills more than technical knowledge in the workplace. de Vries, Blomme and De Loo (2021) demonstrated that the most noteworthy test in enrolling first-year trainee accountants in the workplace was discovering candidates with the necessary technological experience.…”
Section: Inadequate Technological Knowledge and Skillsmentioning
confidence: 99%
“…Inadequate of technological practices in tertiary institutions is another challenge that has been highlighted in the literature (Johnson et al, 2016). According to Mhlongo (2020), trainee accountants are faced with the application of IT skills more than technical knowledge in the workplace. de Vries, Blomme and De Loo (2021) demonstrated that the most noteworthy test in enrolling first-year trainee accountants in the workplace was discovering candidates with the necessary technological experience.…”
Section: Inadequate Technological Knowledge and Skillsmentioning
confidence: 99%
“…For example, the authors of [12] have confirmed the growing demand for accounting graduates who possess teamwork abilities and good communication and interpersonal skills. Likewise, other studies [9,13] demonstrated that compared to other business professionals, accounting students did not feel that their study programs improved their leadership abilities, oral and written communication, and critical thinking. Accounting programs need to be positioned to develop those soft skills that are deemed important by accounting students [15,16] and working professionals [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, graduates are not totally aware of what skills employers consider to be important: students are still focused on technical skills, while employers have been increasingly concentrating on transversal skills [12]. There is some evidence that employers often prioritize soft skills over technical ones in the accounting profession [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations